Етнодемографічна історія українців південної частини далекого сходу Росії (друга половина XIX – початок XX століття) - Аргудяєва, Ю. (Народна творчість та етнографія, 2010)
В статье на основе специальных литературных и статистических источников характеризуются этапы переселения восточнославянских народов, в том числе украинцев, на Дальний Восток России во второй половине XIX – начале XX в. Главное внимание сосредоточено на особенностях развития социально-демографических процессов Based on the special literary and statistical sources there have been determined the stages of migration of the East Slavonic people, including the Ukrainians, to Far Eastern Russia during the second part of the XIXth – the early XXth centuries. The principal attention is concentrated on the issues of the development peculiarities of the social and demographical processes on Russian Southern Far East where the natives from the different parts of Ukraine are the population’s predominant component.